A new genus and species, Panamapisa guaymii gen. nov. sp. nov., the first record of the family Eriopisidae Lowry & Myers, 2013 from Central America - Alves, Jessika; Lowry, James K.; Neves, Elizabeth G.; Johnsson, Rodrigo (Zootaxa, 2021)
Eriopisidae is a widespread amphipod family, whose members have subcylindrical bodies, often do not have eyes, showing elongate third uropods in which the endopod is reduced and the exopod can become very long. This is the first record of Eriopisidae from Central America. Here, we describe the new genus and species Panamapisa guaymii gen. nov., sp. nov. from Bocas del Toro, Panama. The taxon differs from other members of the family in having a greatly enlarged merus on gnathopod 1, marginal setae on the dactyls of pereopod 5 to 7 and a third uropod nearly as long as the body.